The Effect of Egg Shell and Banana Peel Organic Fertilizer on The Growth Of Green Spinach (Amaratus tricolor L.) - Nurseha Nurseha; Prapti Sedijani; Lalu Japa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Long-term use of chemical fertilizers damages soil properties. Efforts to restore soil fertility by using liquid organic fertilizer are needed. Organic fertilizers from waste provide nutrition for plants while reducing environmental pollution. This study aims to analyze the effect of applying liquid organic fertilizer from banana peels, liquid organic fertilizer from egg shells, and the effect of the combination of liquid organic fertilizers. Two Way Anova test results with sig. a value <0.05 indicates that the POC of banana peel increased plant height, number of leaves, fresh weight and dry weight of green spinach. Eggshell POC increased wet weight and dry weight, while the combination of the two POC increased plant height and number of leaves, wet weight and dry weight of green spinach plants. This shows that the application of banana peel liquid organic fertilizer is more influential than the application of egg shell organic fertilizer.